Composition of needle oil of juniperus communis L. from north India - Singh, Gurdip (2005)
GC and GC-MS analyses of volatile oil of needle of Juniperus communis L. from north Indian plains showed presence of forty one components accounting 94% of the oil. The major constituent was sabinene (27.5%), followed by elemol (15.8(, limonene (13.9), bornyl acetate (7.2), myrcene (5.3) and alpha-pinene (4.0).